Hierarchical Nanorods of MoS2/MoP Heterojunction for Efficient Electrocatalytic Hydrogen Evolution Reaction. Issue 32 (6th July 2020) - Liu, Qian; Xue, Ziqian; Jia, Baoming; Liu, Qinglin; Liu, Kang; Lin, Yiyang; Liu, Min; Li, Yinle; Li, Guangqin
Abstract: Hierarchical nanostructures with tailored component and architectures are attractive for energy‐related applications. Here, the delicate design and construction of hierarchical MoS2 /MoP (H‐MoS2 /MoP) nanorods for the hydrogen evolution reaction (HER) are demonstrated. This multiscale design rationally combines the compositional and structural advantages of MoS2 /MoP heterojunction into a hierarchical architecture, which can modulate electronic structure of S, remarkably facilitating the electrocatalytic HER. Benefitting from their unique architecture and electronic structure, the H‐MoS2 /MoP nanorods exhibit excellent performance for HER with ultralow overpotential of 92 mV at current density of 10 mA cm −2 in 1 m KOH and high stability. This work not only provides an efficient approach to constructing hierarchical heterojunctions, but also a multiscale strategy for all‐round regulation of the electronic structure and hierarchical morphology of nanomaterials for energy‐related applications. Abstract : Nanorod‐like hierarchical MoS2 /MoP heterojunctions are synthesized via MoO3 nanorods as the starting sacrificial template. The obtained H‐MoS2 /MoP has high stability and excellent HER activity, due to optimized electronic structure of S and decreased free energy of H adsorption.